2015
DOI: 10.11604/pamj.2015.20.177.4025
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and obstacles to oral antidiabetic medications adherence among type 2 diabetics in ismailia, egypt: a cross section study

Abstract: IntroductionDiabetes is a costly and increasingly common chronic disease. Effective management of diabetes to achieve glycemic control improves patient quality of life. Adherence rates to drug regimens in patients with type 2 diabetes are relatively low and vary widely between populations. There are many factors that could affect patient adherence to drug therapy. The aim of the present study was assessing patterns and obstacles to adherence of type 2 diabetic patients to their oral hypoglycemic drugs.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 20 publications
7
31
3
1
Order By: Relevance
“…In our study, 44.26% of the participants reported that taking many medications interferes with adherence to their antidiabetic agents, which is a smaller percentage than that reported by Cramer (36%) for the same reason [7]. Cramer and Heissam reported that monotherapy had better adherence than multitherapy treatment plans [7,8].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In our study, 44.26% of the participants reported that taking many medications interferes with adherence to their antidiabetic agents, which is a smaller percentage than that reported by Cramer (36%) for the same reason [7]. Cramer and Heissam reported that monotherapy had better adherence than multitherapy treatment plans [7,8].…”
Section: Discussioncontrasting
confidence: 55%
“…A similar study was carried out in Egypt by Heissam et al in 2015 for OHA adherence in 372 participants [8]. Patients achieving a result of more than 75% on the Morisky-Green-Levine scale were considered as having good adherence, as score less than 50% was considered poor adherence, and a score between 50% and 75% was considered decent adherence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The magnitude of this proportion does vary in various places, research in Egypt shows the proportion of men more than women. 8 In this study the proportion of respondents aged ≥60 years was bigger than respondents aged <60 years, this is by the theory that the prevalence of Type 2 diabetes increases in the population with older age. Although Type 2 DM is more common in older age, it is currently increasing in the adolescent and young adult population due to lack of physical activity, unhealthy eating patterns, and increasing obesity.…”
Section: Characteristics Of Respondentsmentioning
confidence: 60%
“…Although Type 2 DM is more common in older age, it is currently increasing in the adolescent and young adult population due to lack of physical activity, unhealthy eating patterns, and increasing obesity. 8,9 Use of Antihyperglycemia The most commonly used type of therapy is monotherapy (70.8%), and the oral antihyperglycemic drug most widely used by respondents is the biguanide group, metformin (72.58%). This result is not surprising because the trend of the use of…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%